Economics and ecosystems efficiency, sustainability and equity in ecosystem management - Hein, Lars.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2010)
"Demonstrates how the concepts of economic efficiency, sustainability and equity can be applied in ecosystem management. The book presents an overview of these three concepts, a framework for their analysis and modelling, and three case studies. Specific attention is given to how complex ecosystem dynamics, such as thresholds or irreversible responses, influence ecosystem management options. The case studies focus on ecosystem dynamics and ecosystem services supply in a forest ecosystem, a Dutch wetland, and a rangeland in the Western Sahel. Integrating ecology and economics, this informative book will appeal to postgraduate students in environmental sciences and environmental economics as well as ecosystem managers."--P. [4] of cover.
1. Introduction -- 2. Ecological-economic concepts -- 3. A quantitative ecological-economic assessment approach. -- 4. Modelling the efficiency and sustainability of forest management -- 5. Case study : eutrophication control in the De Wieden wetland, The Netherlands -- 6. Case study : rangeland management in the Ferlo, Senegal -- 7. Applying the framework in support of environmental management.
Includes bibliographical references (p. 168-198) and index.
Keywords: Ecosystem management -- Economic aspects; Sustainable development; Electronic books